GC-MS Profiling, Invitro Antidiabetic, Antioxidant and Antimicrobial Activities of a Novel Polyherbal Formulation (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
In the present study the methanol extract of a novel polyherbal formulation (PHF) was studied for alpha (α)- amylase and alpha (α)-glucosidase inhibition using an in vitro antidiabetic model. The polyherbal extract were also examined for its antioxidant activity by using free radical 1,1-diphenyl-2-picryl hydrazyl (DPPH) scavenging method. The study revealed that the polyherbal formulation exhibit potent radical scavenging activity using DPPH as substrate. The methanol extract exhibited significant α-amylase and α-glucosidase inhibitory activities with an IC50 value 31.52±0.74µg and 53.13±0.97µg respectively and well compared with standard acarbose drug. Further, antibacterial activity of methanol extract of PHF valuated against standard strains, the tested extract showed more potent inhibitory effects on both Gram (+) bacteria and Gram (-) bacteria. Thus, it could be concluded that due the presence of antioxidant components the plant extract have well prospective for the management of diabetes and the related condition of oxidative stress. This knowledge will be useful in finding more potent antidiabetic principle from the natural resources for the clinical development of antidiabetic therapeutics.